Study on three-dimensional physical simulation experiment of remaining oil distribution in narrow channel reservoir - Ma, Kuiqian; Wang, Jijun; Si, Shaohua; Yang, Lei; Zhao, Zhuo; Ling, Haochuan; Wu, Zheng (Frontiers in Earth Science, 2025)
The sand bodies of narrow channel reservoirs are predominantly composed of distributary channels, with effective sand bodies often forming narrow strips. The development of offshore oilfields typically involves large well spacing, which, combined with the distribution form of the river channels and the well pattern, significantly influences the sweep efficiency of water flooding during the high water cut stage. This leads to a complex distribution of remaining oil, thereby increasing the difficulty of reservoir development. This study focuses on the BZ offshore narrow channel reservoir and introduces a novel three-dimensional visual experiment platform designed for the physical simulation of water flooding. Through this platform, we conducted a series of physical experiments to investigate the effects of varying channel widths, permeability differences, and well patterns on water flooding. Our experiments have successfully elucidated the distribution patterns of remaining oil both in the plane and longitudinal directions of the channel during the high water cut stage. The experimental results show that with the increase in width, the shape of the water-swept area changes from a narrow strip to a spindle, and the remaining oil around the production well begins to accumulate. The larger the permeability difference is, the more injected water preferentially advances along the high permeability zone, the worse the sweeping degree at the channel’s edge is, and the higher the accumulation degree of the remaining oil is. Through the well type adjustment, the water cut is reduced and the remaining oil near the production well and the edge of the channel is utilized. After the well pattern adjustment, the utilization of remaining oil in the river channel is also improved. This research not only provides critical insights into the dynamics of water flooding in narrow channel reservoirs but also establishes a foundational methodology for evaluating the effectiveness of CO2 flooding following water flooding. The development of the three-dimensional visual experiment platform represents a significant advancement in reservoir simulation techniques, offering a robust tool for future studies aimed at optimizing oil recovery in complex reservoir environments.